Recent Economic Intimate Partner Violence and Posttraumatic Stress Symptoms Among a Racially and Ethnically Diverse Sample of U.S. Women Experiencing Intimate Partner Violence - Willie, Tiara C. (Journal of interpersonal violence, 2023)
Posttraumatic stress disorder (PTSD) is a prevalent consequence of physical and sexual intimate partner violence (IPV); however, little is known about the unique contributions of economic IPV. Furthermore, women’s economic self-sufficiency may explicate the potential relationship between economic IPV and PTSD symptoms. Guided by the Stress Process Theory and Intersectionality, this study examined associations between economic IPV and women’s PTSD symptoms and assessed economic self-sufficiency as a mediator. Participants were 255 adult women experiencing IPV recruited from metropolitan Baltimore, MD, and the state of CT who participated in two different studies. Participants completed surveys on IPV, economic self-sufficiency, and PTSD. Path analyses were conducted to examine direct and indirect associations of economic IPV with economic self-sufficiency and PTSD. Economic IPV was uniquely associated with PTSD symptoms while controlling for other forms of IPV. Economic self-sufficiency significantly partially mediated the association between economic IPV and PTSD symptoms such that economic IPV was associated with PTSD symptoms through economic self-sufficiency. Economic IPV may limit women’s ability to make autonomous decisions related to finances, which could be distressing. The mental health impact of economic IPV may be particularly debilitating for women with low economic self-sufficiency as their posttraumatic stress occurs within the context of feeling unable to meet their financial goals and also having a partner control their economic resources. Fostering economic empowerment and asset building may be a strengths-based approach to reduce the PTSD symptomatology among women experiencing IPV.